PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM PEMENUHAN KEBUTUHAN DASAR PENGUNGSI DI KOTA KUPANG DITINJAU DARI PERATURAN PRESIDEN NOMOR 125 TAHUN 2016 - Redemptus D. L. Regaletha; D. W. Tadeus; Gerald Aldytia Bunga; Jeffry A. Ch Likadja (LPPM Universitas Ekasakti Padang, 2023)
One country that is often a transit country for people seeking asylum elsewhere is Indonesia. Due to its location, Indonesia can become an illicit trade corridor and a stopover for people seeking asylum in Australia. As the influx of these refugees is deemed to pose a danger to national security and resilience, these illegal arrivals are certainly bad for Indonesia. Every person entering or leaving Indonesia is required by law to have a valid travel document. Indonesian laws and regulations governing the treatment of international refugees are inadequate. The purpose of this study is to analyse the role of IOM in fulfilling the basic needs of refugees in Kupang City in terms of Presidential Regulation Number 125 of 2016 concerning the handling of refugees from abroad